Literarisches Transferieren – Überlegungen zu einem Modus in Theorie und Praxis - Schenker, Ina (Acta Neophilologica, 2024)
The article highlights the growing significance of transfer and the Third Mission in German universities, especially in literary studies. It argues that literary disciplines have been slow to define their approach to transfer, likely due to resource limitations or resistance to change. To address this, the article proposes “Literary Transferring” as a creative, philological method for integrating transfer concepts into literary studies, emphasizing the need for theoretical engagement to inform empirical practice and foster collaboration between authors, literary institutions and researchers.